The influence of architectural heritage and tourists’ positive emotions on behavioral intentions using eye-tracking study - Xinyu Li; Pohsun Wang; Long Li; Jing Liu (Scientific Reports)
Abstract The city’s rapid development would lead to irreversible changes in architectural heritage. As one of the ways to promote sustainable development, world heritage tourism has opened up a new perspective for the protection, inheritance and development of architectural heritage. Taking the study of architectural heritage in the Historic Centre of Macau as an example, employing eye-tracking experiment and semantic differential method (SD method) to explore the relationship between tourists’ perceptions of visual elements of architectural heritage, positive emotions, and behavioral intentions. The results show that in terms of visual elements, the architectural style of the wall (p = 0.013 < 0.05, B = 0.165), the proportional balance of the windows (p = 0.047 < 0.05, B = 0.120), the exquisite decoration of the door (p = 0.028 < 0.05, B = 0.125), and the proportional balance of other buildings (p = 0.042 < 0.05, B = 0.121) have a positive impact on tourists’ behavioral intention. In terms of positive emotions, positive (p = 0.001 < 0.05, B = 0.177), intense (p = 0.000 < 0.01, B = 0.228), and enthusiastic (p = 0.008 < 0.05, B = 0.156) emotions were positively correlated with behavioral intention. The research results can provide a scientific basis and decisional reference for the protection and tourism development of architectural heritage in the Historic Centre of Macau.